Physical fitness of rhythmic gymnasts depending on age and level of sports achievements - Sterkowicz-Przybycien, K.; Fundament, P. (Journal of Kinesiology and Exercise Sciences, 2020)
Aim. The aim of this study was to compare the indices of physical development, frequency and time duration of training, and the results of physical fitness tests depending on age and level of sports achievements among rhythmic gymnasts. Materials and methods. The study comprised 36 rhythmic gymnasts: Gr1 (n=13, 9.0±1.0 years), Gr2 (n=11, 11.36±0.5 years), Gr3 (n=12, 14.27±0.7 years). After standardised sports interview, the groups with lower level of sports achievements (LSL) (n=20) and higher level of sports achievements (HSL) (n=16) were defined. Measurements of body height and mass were performed. The study participants performed the broad jump test, Unipedal Stance Test with Eyes Open (UPST-EO) and Eyes Closed (EC), and the rhythmic gymnastics specific coordinative test with a hoop. Results. The number of training sessions per week and their duration did not depend on age. The results of the broad jump were significantly different for groups Gr1, Gr2 and Gr3 (F=27.02, p<0.01). The average results for the 3 trials of UPST-EO in Gr2 and Gr3 were better than in Gr1 (F=5.51, p=0.008). The average result of UPST-EC for Gr3 was also significantly better than for Gr1 (W=9.53, p=0.008). The hoop test showed differences for all age groups Gr1<Gr3<Gr2 (F=11.55, p<0.001). HSL athletes were significantly different from LSL in frequency and duration of training, average results from 3 trials of UPST-EO, UPSTEC and the best result of UPST-EC (p<0.05). Conclusions. Differences between groups in physical fitness tests results depended on gymnasts` age and showed their usefulness in the control of training at a particular stage of sports development. HSL gymnasts predominated over LSL in results of the one-leg standing position postural balance test with eyes opened and closed. The detected differences can be useful for coaches in identifying and developing gymnastic talent.